(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines effective methods for developing students’ literary and analytical skills in a financial education environment. It emphasizes the use of modern pedagogical and information technologies for analyzing students’ independent thinking, in-depth text analysis, interactive communication, and the development of creative skills.